Good Governance in Thailand’s Durian Exportation - Chaichuy, Thanongsak; Trimek, Jomdet (Journal of Buddhist Education and Research (JBER), 2025)
This research analyzes the problems of governance in Thailand's durian exports and proposes guidelines for developing good practice standards and fair-trade policies. Data was collected through in-depth interviews with durian packing house operators and related agencies, using a purposive sampling method with a total of 12 participants, including 8 durian export business operators and 4 representatives from pertinent agricultural policy agencies. The findings indicated that the durian export sector in Thailand is subject to unjust trade practices, which include production control and bulk purchasing, grading and price control, complex regulatory systems, misrepresentation of durians from neighboring countries, and interventions by gray-market investors. Durian pricing, transportation and inspection systems, quality control to ensure compliance with standards, chemical residue and immature durian inspections, and clear pre-harvest and export regulations within the country are all critical components of best practice standards for durian exportation in Thailand. The research recommends the implementation of quality control measures for exported durians, market expansion and diversification, financial assistance for business operators, support for infrastructure and logistics systems, and collaborative development of durian exports between the government and the private sector to implement fair trade policies for Thailand's agricultural sector in durian exports.